2019
DOI: 10.24996/ijs.2019.60.5.6
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Antibiotic-Resistant Genes in Salmonella Typhi Isolated From Typhoid Patient in Samawa City

Abstract: A total of 100 blood samples taken from patients with suspected typhoid fever aged between (1-60) years, were involved in this study. Blood samples were cultured directly on brain heart infusion broth. After that sub cultured of isolates on MacConkey agar and XLD agar and S.S agar to find the Salmonella typhi then identified by the biochemical and antibiotic sensitivity test. Resistant genes were identified by using aacc2 gene and cat gene. Results showed that there was 7 Salmonella typhi isolates from blood c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…Most S.typhi isolates, including multidrug-resistant strains, were susceptible to ciprofloxacin and nalidixic acid but resistant to levofloxacin and chloramphenicol. Our results are the same as those of studies done in Samawa, Iraq, which found that clinical strains of S.typhi had high levels of resistance to chloramphenicol, ampicillin, and levofloxacin (34). Malehmir et al found that paediatric cases of S.typhi in Tehran, Iran, were less sensitive to ciprofloxacin and nalidixic acid, more sensitive to chloramphenicol antibiotics, and had a very low proportion of MDR strains (35).…”
Section: Out Of 246 Blood Specimens Collected From a Patient With Sus...supporting
confidence: 90%
See 1 more Smart Citation
“…Most S.typhi isolates, including multidrug-resistant strains, were susceptible to ciprofloxacin and nalidixic acid but resistant to levofloxacin and chloramphenicol. Our results are the same as those of studies done in Samawa, Iraq, which found that clinical strains of S.typhi had high levels of resistance to chloramphenicol, ampicillin, and levofloxacin (34). Malehmir et al found that paediatric cases of S.typhi in Tehran, Iran, were less sensitive to ciprofloxacin and nalidixic acid, more sensitive to chloramphenicol antibiotics, and had a very low proportion of MDR strains (35).…”
Section: Out Of 246 Blood Specimens Collected From a Patient With Sus...supporting
confidence: 90%
“…In India, the qnrB gene was amplified in 70% of S.typhi strains isolated from blood cultures, but neither the qnrA nor the qnrS gene was amplified (42). In Iran, qnrS was detected in 56.5% of the S.typhi strains, qnrA was found in 30.4%while qnrB was in 1.1% (34). In Brazil, qnrS was found in 53.3% of S.typhi strains, qnrB was found in 40%, and qnrA was not (43).…”
Section: Out Of 246 Blood Specimens Collected From a Patient With Sus...mentioning
confidence: 99%
“…"The occurrence of S. typhi from stool of patients in relationship to their age was higher at age 21-30 years, and this is in agreement with a study which reported high occurrence of S. typhi in patients of age > 10-41 years [17] and 21-31 years" [21].…”
Section: Molecular Detection Of Plasmid Mediated Quinolone Resistant ...supporting
confidence: 87%
“…"In India, the qnrB gene was amplified in 70.0% of S.typhi strains isolated" [28]. In Iran, qnrA was found in 30.4% of the S.typhi isolates, qnrS was detected in 56.5%, while qnrB was detected in 1.1% [21].…”
Section: Molecular Detection Of Plasmid Mediated Quinolone Resistant ...mentioning
confidence: 99%
“…In addition, epidemical studies demonstrated that S. typhi carriers are more likely to be infected with gallbladder cancer compared to the uninfected ones [17]. Isolation of S. typhi from the cultured tissues was in conformity with the results of [24]. The diagnosis of the S. typhi by Vitek2 compact system showed 99% conformity as this system is considered one of the rapid and accurate technique in terms of diagnosing bacteria.…”
Section: Discussionmentioning
confidence: 53%